Implantation of leadless pacemakers via inferior vena cava filters is feasible and safe: Insights from a multicenter experience. (28th October 2020) - Houmsse, Mahmoud; Karki, Roshan; Gabriels, James; Reinig, Michael; Patel, Dilesh; Hussain, Sarah K.; Gandhi, Gaurang D.; Lloyd, Michael S.; Makary, Mina S.; Okabe, Toshimasa; Tamirisa, Kamala; Joza, Jacqueline; et al.
Abstract: Background: The leadless Micra transcatheter‐pacing system (Micra‐TPS) is implanted via a femoral approach using a 27‐French introducer sheath. The Micra Transcutaneous Pacing Study excluded patients with inferior vena cava (IVC) filters. Objective: To examine the feasibility and safety of Micra‐TPS implantation through an IVC filter. Methods: This multicenter retrospective study included patients with an IVC filter who underwent a Micra‐TPS implantation. Data for clinical and IVC filter characteristics, preprocedure imaging, and procedural interventions were collected. The primary outcome was a successful leadless pacemaker (LP) implantation via a femoral approach in the presence of an IVC filter. Periprocedural and delayed clinical complications were also evaluated. Results: Of the 1528 Micra‐TPS implants attempted, 23 patients (1.5%) had IVC filters. The majority (69.6%) of IVC filters were permanent. Six (26.1%) patients underwent preprocedural imaging to assess for filter patency. One patient's filter was retrieved before LP implantation. The primary outcome was achieved in 21 of 22 patients (95.5%) with an existing IVC filter. An occluded IVC precluded LP implantation in one patient. Difficulty advancing the stiff guidewire or the 27‐Fr sheath was encountered in five patients. These cases required repositioning of the wire ( n = 2), gradual sheath upsizing ( n = 2), or balloon dilation of the filter ( n = 1). Postprocedure fluoroscopy revealed intact filters in all cases. During a median 6‐month follow‐up, there were no clinical complications related to the filter or the Micra‐TPS. Conclusion: This multicenter experience demonstrates the feasibility and safety of Micra‐TPS implantation via an IVC filter without acute procedural or delayed clinical complications.